Life : a user's manual : philosophy for (almost) any eventuality - Baggini, Julian; Macaro, Antonia (London : Ebury Press, 2020)
Since the beginning of time, people have asked questions about how they should live and, from Ancient Greece to Japan, philosophers have attempted to solve these questions for us. The timeless wisdom that they offer can help us to find our own path. In this insightful, engaging book, renowned existential psychotherapist and philosophical counsellor Antonia Macaro and bestselling philosopher Julian Baggini cover topics such as bereavement, luck, free will and relationships, and guide us through what the greatest thinkers to ever walk the earth have to say on these subjects, from the Stoics to Sartre --
Includes index.
Keywords: Theory (Philosophy); Philosophy